ORGANIZATION OF DISTRICT COURTS (1846-1858) - Popović, Miroslav M. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In this paper we tried to present the organization of district courts in the period 1846-1858, which is marked by the two reconstructions of judicial system. In the first reconstruction of 1846, new court organization laws were brought and the second reconstruction of 1858 meant the foundation of the Court of Cassation. Organization of district courts is considered as very important; district courts of the first degree bore the burden of judicial system and other judicial instances were dependent on efficiency of district courts. Organization of district courts was a reflection of the inner policy of Ustavobranitelji. Legislative and executive authorities faced various challenges in the judicial practice and brought solutions by which legal norms were interpreted or changed. The search for the right solutions and learning on own mistakes led to the definitive court organization in 1865.